Implementation of Differentiated Learning at TK Islam Plus E-School - Sitti Nurhidayah Ilyas; Angri Lismayani (PT ARRUS Intelektual Indonesia, 2023)
This study aims to determine the description of the implementation of differentiated learning based on the aspects of KPPLB EPEC: (a) content (b) process (c) product and; (e) learning environment in Islamic Kindergarten Plus E School Pinrang. This type of research is qualitative-descriptive. In collecting data, the researcher acted as a research instrument. Data were obtained through two sources, namely informants and documents. Data collection techniques were carried out through observations on videos of learning activities, interviews and documentation. The data obtained were then analysed using the concept of Miles and Huberman. Data validation was carried out by data credibility test, transferability test, dependability test and confirmability test. The results of the study are expected to describe the applicative stages or steps taken by teachers in the implementation of differentiated learning. This study focused on getting an overview of the differentiated learning process by analysing the teaching modules developed based on the results of diagnostic assessments conducted by teachers, learning implementation as well as teacher evaluation and reflection as a basis for developing further teaching modules.